Studi Perilaku, Palatabilitas Pakan dan Bentuk Sarang Kesukaan Gelatik Jawa (Padda oryzivora) - R. Susanti; Margareta Rahayuningsih; Nugroho Edi Kartijono; Andi Haryoko; Arif Rahman Hakim; Tri Oktaviantari (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2006)
A study was conducted to disclose the habit, food type palatability, and the nest type preference of gelatik jawa (Padda oryzivora). As many as 54 gelatik jawas from Surabaya, Malang, Ngawi, Bekasi, Karawang, Cirebon, Bogor, Semarang, Magelang, Yogyakarta and Prambanan were captured using soft nylon net and then caged for two weeks for adaptation. Each bird was given a ring to make it easier to identify. After the adaptation period, the birds were moved to a wider cage. Every day the habit and mating behaviour as well as the preference of food and nest were observed. The highest  frequency of daily feeding (997.75 ± 72.23) and moving (795.50 ± 138.27); and the lowest  frequency of daily self care (4.126 ± 138.27) and communicate (93.75 ±  7.59) were recorded at 08.00 – 10.00. Food palatability and preference over nest, habit, and biological clock of gelatik jawa could be the basis of ex-situ conservation. The monogamy character of gelatik jawa could also serve as the basis of ex-situ conservation that male and female in one cage must be in equal number.